2014
DOI: 10.1002/asia.201402187
|View full text |Cite
|
Sign up to set email alerts
|

Dual Association Modes of the 2,5,8‐Tris(pentafluorophenyl)phenalenyl Radical

Abstract: The 2,5,8-tris(pentafluorophenyl)phenalenyl radical was obtained by a straightforward synthesis in 11 steps from 2,7-dibromonaphthalene. This radical crystallized as a σ dimer from a solution in MeCN and as a π-stack from a melted liquid. The π stack was not confined to dimerization, but extended into a uniform 1D stack with an interplanar distance of 3.503 Å. This unique duality in association mode arose from the thermodynamic stability of the phenalenyl moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 39 publications
1
44
0
Order By: Relevance
“…The X ray crystallographic analysis of the crystal showed that 5 adapts a σ dimer form (5 2 ) in the solid state (Figure 5a). 25 The 1 H NMR spectrum of the colorless crystals in CDCl 3 showed six sharp singlet signals in the temperature range 233 298 K, consistent with the σ dimer form. No peak originating from a π dimer form was observed.…”
Section: Challenge To Ideal One Dimensional (1d) Stack Of Phenalenyl mentioning
confidence: 96%
“…The X ray crystallographic analysis of the crystal showed that 5 adapts a σ dimer form (5 2 ) in the solid state (Figure 5a). 25 The 1 H NMR spectrum of the colorless crystals in CDCl 3 showed six sharp singlet signals in the temperature range 233 298 K, consistent with the σ dimer form. No peak originating from a π dimer form was observed.…”
Section: Challenge To Ideal One Dimensional (1d) Stack Of Phenalenyl mentioning
confidence: 96%
“…In recent years, a plethora of functional molecular materials based on PLY and its derivatives have been realized, displaying diverse fascinating optical, conducting, and magnetic properties. 1,[18][19][20][21]41,42 We note that the new molecular species introduced in this work may be equally exploited as building blocks of new functional materials for the realization of unique material properties. The double π−π bonding in fact consists of two separate single "bonds" of comparable strength as the single π−π-bonded PLY dimer.…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%
“…[15][16][17] In a few cases, 1D π-stacking columns are formed with large intermolecular separations of~3.78 (ref. 13) and 3.65 Å, 19 due to bulky protection groups, the latter of which shows a band around 800 nm. 19 π-Stacked structures of π-conjugated PNL dimers (1/2 unpaired electron per PNL unit) [20][21][22] and those of singlet-diradical bisphenalenyls 23 (one unpaired electron per PNL unit) exhibit NIR absorption bands.…”
mentioning
confidence: 99%
“…13) and 3.65 Å, 19 due to bulky protection groups, the latter of which shows a band around 800 nm. 19 π-Stacked structures of π-conjugated PNL dimers (1/2 unpaired electron per PNL unit) [20][21][22] and those of singlet-diradical bisphenalenyls 23 (one unpaired electron per PNL unit) exhibit NIR absorption bands. Bis(dithiazolyl) radicals 24,25 form 1D π-stacks with intercolumnar S•••S and S•••N contacts, showing lowenergy absorption bands around~2500 nm (~0.5 eV).…”
mentioning
confidence: 99%
See 1 more Smart Citation